Centrally-mediated cardiovascular actions of the angiotensin II type 2 receptor - Steckelings, U. Muscha (Trends Endocrinol Metab, 2017)
Sustained increases in activity of the sympathetic neural pathways that exit the brain and which increase blood pressure are a major underlying factor in resistant hypertension. Recently available information on the occurrence of angiotensin II type 2 receptors (AT2R) within or adjacent to brain cardiovascular control centers is consistent with findings that stimulation of these receptors lowers blood pressure, particularly during hypertension of neurogenic origin. Up until recently, brain AT2R had not been considered by many to play a role in the central control of blood pressure. Demonstration of these powerful anti-hypertensive effects of brain AT2R opens the door to reconsideration of their role in blood pressure regulation, and their consideration as a novel therapeutic avenue for resistant hypertension.